PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE HUAWEI (Studi Pada Mahasiswa Universitas Diponegoro Dan Universitas Negeri Semarang) - Ahmad Surya Gunawan; Wahyu Hidayat (Universitas Diponegoro, 2019)
In modern times like today, the demand for various types of communication tools is increasing. This causes competition to compete the market share in business world in the telecommunications sector. Huawei is a Chinese smartphone brand that is in demand by the public both in terms of trusted product quality and low prices. Based on statistics from the International Data Corporation (IDC) which describes the market share of smartphone users in the world, Huawei ranks second in the world with a market share of 15.8%. The magnitude of Huawei smartphones market share is due to high purchasing decisions that are influenced by product quality, price, place and promotion. The purpose of this study is T to determine the effect of product quality and price on purchasing decisions of Huawei smartphones. The type of research used is correlational studies with quantitative methods. The sampling technique uses non-probality sampling, namely accidental sampling and purposive sampling. This study uses a sample of 100 respondents, consisting of Universitas Diponegoro and Universitas Negeri Semarang students who have purchased Huawei Smartphones. Data collection techniques using a questionnaire. This study uses qualitative and quantitative analysis, the stages begin the validity and reliability test followed by a regression analysis using SPSS 22.0. The results showed that all proposed indicators were valid and the three variables proposed were reliable. Regression test results indicate product quality and price have a positive and significant influence on purchasing decisions. Researcher suggest to PT Huawei Tech Investments is to improve product quality on product durability, complete features, and component availability. Maintaining prices by adjusting product prices and quality, and providing ease of payment. Improve purchasing decisions by adding sales outlets, increasing advertising and promotions